0
$\begingroup$

The solution of the differential equation $(\frac{dy}{dx})^2=(1-y^2)(1-k^2+k^2 y^2)$ for the initial condition $y(0)=1$ is $y(x)=cn(x, k^2)$ where $cn$ is Jacobi elliptic function. I found the general solution of this equation is $y(x)=\sqrt{1-\frac{1}{k^2 sn^2(x+c1, k^2)}}$ where c1 is the integration constant. But when I use the initial condition $y(0)=1$ in it, I can't get a valid value of integration constant c1.

$\endgroup$
1
$\begingroup$

$$(\frac{dy}{dx})^2=(1-y^2)(1-k^2+k^2 y^2)$$ The general solution is $y(x)=cn(x+c_1\:,\:k^2)$

with the initial condition $y(0)=1\quad\to\quad c_1=0$ $$y(x)=cn(x,k^2)$$ The relationship between $cn$ and $sn$ is : $cn^2(x,k^2)=1-sn^2(x,k^2)$ , thus : $$y(x)=\sqrt{1-sn^2(x+c_1\:,\:k^2)}$$ $y(x)=\sqrt{1-\frac{1}{k^2 sn^2(x+c1, k^2)}}$ is false.

Finally, with the initial condition : $$y(x)=\sqrt{1-sn^2(x,k^2)}$$ $sn(0,k^2)=0 \quad\to\quad y(0)=1$ .

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.